Cost-Effectiveness of Carrier Screening for Cystic Fibrosis in Australia - Norman, Richard; Van Gool, K.; Hall, J.; Delatycki, M.; Massie, J. (Elsevier, 2012)
Background: Carrier screening for cystic fibrosis is not widely available in Australia, partly due to concerns regarding its cost-effectiveness. The benefit of information from pregnancy to pregnancy has not been widely considered in existing cost-effectiveness analyses.Methods: A decision tree was constructed estimating costs and outcomes from screening, including both initial and subsequent pregnancies. Effectiveness was expressed in terms of CF births averted. Costs were collected using a health service perspective. All costs and outcomes were discounted at 5% per annum.Results: Screening reduced the annual incidence of CF births from 34 to 14/100,000 births (an aggregate number of CF births of 100.9 and 41.9 respectively). In initial pregnancies, costs in the screening arm (A$16.6 million/100,000 births) exceed those in the non-screening arm (A $13.4 million/100,000 births). The incremental cost per CF birth in initial pregnancies is therefore approximately A$150,000. However, this was reversed for subsequent pregnancies, in that the pre-collected information reduces the incidence of CF in subsequent pregnancies at low additional costs.When aggregated, the results suggest screening is likely to be cost-saving.Conclusions: The introduction of national carrier screening for cystic fibrosis should be considered, as it is likely to reduce CF incidence at an acceptable (potentially negative) cost.